Rapid, illegible handwriting as a symptom of obsessive-compulsive disorder - Bavle, Amar (Medknow Publications & Media Pvt Ltd, 2014)
This is a case report of a 13 year male child who had co-morbid OCD and trichotillomania. On evaluation, he had rapid, illegible handwriting as a symptom of OCD, which has hitherto not been reported.